The Effect of Dual-Task Texting on Cervical Muscle Activity in Smartphone Users - Susilo, Taufik Eko; Hanifa, Miftahul Fauziah; Wijianto, Wijianto; Sudaryanto, Wahyu Tri; Fatmarizka, Tiara; Fitriyah, Qonitah Faizatul; Al Farizy, Muhammad Hasbi; Hendra, Zulnanda; Jannah, Nadiya Izzatul (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Current technological developments are very fast making it easier for people to carry out all activities via smartphones. One of the frequently used smartphone functions is typing and sending messages. Typing and sending messages can be done anytime and anywhere. Typing messages on a smartphone while walking falls into the dual-task category. This study aims to analyze the effect of using dual-task texting on cervical region muscle activity on smartphone users, where smartphone users type messages while walking. Methods: The method used is a single-group repeated experimental design. A total of 36 subjects consisted of 19 women and 17 men with an age range of 21.28 ± 0.97 years. The parameter measured is the upper trapezius muscle activity. Subjects were asked to walk in five conditions, namely baseline walking, texting flashcard 1, texting flashcard 2, texting flashcard 3, and texting flashcard 4. All experiments recorded upper trapezius muscle activity using an electromyograph. Results: The results of repeated measure ANOVA stated that typing on a smartphone had a significant effect (p < 0.05) on young respondents increasing activity of the upper trapezius muscle. Conclusion: Dual-task texting significantly affects cervical region muscle activity, particularly in the upper trapezius muscle on the right side, which has the potential to increase the risk of muscle fatigue in smartphone users.